2010
DOI: 10.1093/rheumatology/keq724
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric and Adolescent Rheumatology [143-150]: 143. Knee Joint in JIA: A Prospective Evaluation of Clinical Examination, Ultrasound and Mri Assessment. A Newly Developed Knee MRI Scoring System in JIA

Abstract: Background: Osteoporotic fractures and falls are as heads and tails of a coin. Among the elderly, the greatest risk of fracture comes from falls, rather than osteoporosis, hence, bone mineral density measurement should not be used alone to estimate fracture risk or guide treatment decisions. Evidence shows that at least 15% of falls in older people can be prevented, with individual trials reporting relative reductions of up to 50%. We developed a model that predicts the falls risk among patients referred for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several studies compared US with MRI in the detection of inflammation, particularly at the knee 13 14 33 34. These studies have shown MRI to be better in detecting knee inflammation than US (mean detection rate 1.20-fold, range 0.63–1.56-fold) and in particular MRI was better than US in differentiating pannus from effusion 13.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies compared US with MRI in the detection of inflammation, particularly at the knee 13 14 33 34. These studies have shown MRI to be better in detecting knee inflammation than US (mean detection rate 1.20-fold, range 0.63–1.56-fold) and in particular MRI was better than US in differentiating pannus from effusion 13.…”
Section: Resultsmentioning
confidence: 99%